Ensuring accuracy of cephalography system measurements - Оникієнко, Юрій Юрійович (Technology audit and production reserves, 2014)
The application of existing approaches for calibrating video cameras for a cephalography system is considered and the results of our studies in this field are given. The main objective of the study lies in developing scientific ways of determining the internal and external parameters of video cameras with the ability of adjusting influence of the total distortion on an output image of a cephalography system. The application of modern software applications allows combining different approaches when calibrating cameras. The main steps of conducting calibration procedures and a mathematical tool for finding a camera matrix are considered and defined in the paper. The given steps in the form of methods allow reducing the final error, resulted from the total distortion by combining automatic and manual modes of estimating key points at calibrating. The research results can be used by medical experts, engaged in researching static and dynamic functions of a human-being.